Diagnostický význam PCR u lymeské boreliózy : metodická a klinická studie - Pícha, Dušan; Moravcová, Lenka; Lásiková, Šárka; Žďárský, Emanuel; Roháčová, Hana; Deutschmannová, Jaroslava; Hančil, Jiří; Skalská, Sylvia (Iga MZ ČR, 2003)
The study is focused on the clinical and methodological testing of in home PCR technique for diagnostics of lyme borreliosis. It deals with the specifity and sensitivity of PCR and ELISA methods in diagnostics tigether with applicability of the results.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: polymerázová řetězová reakce; Lyme Disease; sérologické testy; lymeská nemoc; biologie; Serologic Tests; Polymerase Chain Reaction; Lyme Neuroborreliosis; infekční lékařství; lymská neuroborelióza